Environmental Monitoring of spatial data for the application of NATURA 2000 network in Cyprus using Remote Sensing and GIS - Hadjimitsis, Diofantos G.; Themistokleous, Kyriacos; Onoufriou, Toula (My University, 2008)
In Cyprus, the landscape is continually changing under the influence of several factors (eg, forest fires, urbanization, building development); this situation contributes to a need for updated, consistent and accurate intermediate-scale land cover information. Production of these maps usually requires mapping for the whole area, in a process that usually constitute major undertakings implying major investments when in fact updated maps can be obtained by detecting, interpreting and inserting areas of change in existing maps. Analysis of multi-spectral satellite imagery for accurate land cover mapping and change detection, combining with Geographic Information Systems (GIS) provide an adequate environment to address the problem of land cover change detection. Indeed, this paper presents a case study for the application of integrated remote sensing and GIS data for the classification and monitoring of the land-use changes to support the application on the NATURA 2000 network in some small villages in Cyprus. The study was conducted in Mammari/Denia area in Nicosia. Data analysis was conducted using GIS software.
Keywords: Environmental Monitoring